Ophthalmologic Observations in a Patient with Partial Mosaic Trisomy 8. (13th February 2013) - Abu-Amero, Khaled K.; Kondkar, Altaf A.; Salih, Mustafa A.; Al-Husain, Muneera; Al Shammari, Muneera; Zeidan, Ghassan; Oystreck, Darren T.; Hellani, Ali M.; Kentab, Amal Y.; Bosley, Thomas M.
Abstract: Background: To carefully assess the phenotype and genotype of a patient with partial mosaic trisomy 8 with particular attention to ophthalmologic features. Methods: Ophthalmologic and neuro-ophthalmologic examination; neuroimaging; conventional karyotyping; and array comparative genomic hybridization (CGH). Results: The proband was the only affected child of a non-consanguineous family. At birth she was noted to have facial dysmorphism including telecanthus, low set ears, prominent nares, and an everted lower lip. She had an accommodative esotropia with otherwise normal globes, optic nerves, retinae, and orbits. She also had delayed motor milestones and mild mental retardation associated with agenesis of the corpus callosum. Both karyotyping and array CGH documented mosaic partial trisomy of chromosome 8 that included all of the "q" arm and part of the proximal "p" arm. Conclusions: This girl had a number of the classic features of mosaic trisomy 8, including an accommodative esotropia with none of the other ocular and orbital anomalies described in patients with mosaic trisomy 8. This report constitutes an initial effort to create a virtual database of patients with mosaic chromosome 8 in which careful phenotype-genotype correlation employing high resolution array CGH may help identify clues regarding the genetic etiology of ophthalmologic features of this syndrome.